Reflections on human development - Haq , Mahbub ul (Delhi, 1999)
This book is based on several talks and papers presented by the author. It is organized in two parts, the first dealing with an emerging development paradigm, and the second with the imperative for a new international dialogue in topics central to human development such as a peace agenda for the Third World. The new edition includes a prologue on the human development profile of nations, especially those in South Asia in the late 1990s, and indicators for the turn of the century.
Keywords: Human development